Usefulness of shaping the glide path before using rotary nickel-titanium endodontic files - Javier Laureano Nino Barrera; Mara Catalina Aguilera Canon; Carlos Julio Cortes Rodriguez (Editorial Ciencias Médicas, 2014)
Introduction: materials, techniques and designs continue to be studied with the purpose of reducing the incidence of fracture in endodontic instruments. Shaping of the glide path has been proposed for this end; however, its usefulness has been a matter of controversy. Objective: based on the finite element method, carry out a theoretical analysis of the usefulness of shaping the glide path before using rotary nickel-titanium endodontic files. Methods: numerical simulation was performed based on finite element analysis, to achieve which mathematical models were built of rotary nickel-titanium files S1 and S2 of the Protaper™ series. Autodesk™ Simulation Multiphysics software was used to program the mechanical properties of the files, as well as a fracture failure limit of 1270.588 MPa. The torque recommended by the manufacturer was then applied and the instrument tip fixed into place (without shaping the glide path) with restrictions on all degrees of freedom. In order to simulate glide path shaping, restrictions were applied to all degrees of freedom at a certain distance from the instrument tip, thus simulating that the instrument tip remained free. Results: on fixing the file tips, maximum efforts were 1545.77 Mpa for S1 and 1306.47 Mpa for S2. Instrument fracture was observed. When files were fixed at a distance from the tip, no fracture was observed. Conclusions: it was theoretically demonstrated that when file tips are prevented from being caught, fracture is prevented as well, and such catch is avoided by shaping the glide path. It is therefore concluded that the procedure is useful to prevent the fracture of rotary nickel-titanium instruments.